Relationship between plasma calcium and carcinoembryonic antigen among colorectal cancer patients - Wichendu, Promise N.; Amadi, Collins (International Surgery Journal, 2018)
Background: Low serum calcium is hypothesized to influence colorectal carcinogenesis. Hence, this study was set out to investigate the pattern of plasma calcium in patients with colorectal cancer, and to determine the relationship between the mineral with carcinoembryonic antigen (CEA) among patients with colorectal cancer. Methods: This was a retrospective study of 45 colorectal cancer patients who presented to a tertiary hospital in Nigeria. The laboratory characteristics of these patients were evaluated. Records of sex, age, serum albumin, plasma total calcium, and serum CEA test results from 1st January 2008 to 31st December 2017 were retrieved from laboratory and medical records and analyzed with SPSS software version 20. Results: There were a total of 45 records of colorectal patients in this study, among them were 62.2% males and 37.8% females. The majority (57.8%) of the study cohorts are within the age group 50 to 59 years. Low total calcium was observed in 37.8% of the study cohort while 66.7% tested positive for CEA. The positive CEA group had lower total calcium level than those with negative CEA results (p = 0.001). Negative but weak correlations of total calcium and serum CEA was observed among the overall study cohort (r = -0.485; p = 0.001) and those with positive test for CEA (r = -0.384; p = 0.036). Conclusions: The evidence from this study suggests that low serum calcium could be a risk factor for colorectal cancer and is also associated with higher serum level of the CEA biomarker.